Skirt in TAVI: a toll-free packaging - Bruno García del Blanco; Hugo Cuéllar Calabria (REC: Interventional Cardiology (English Ed.), 2023)
The article signed by García-Guimarães et al.1 recently published in REC: Interventional Cardiology is a living example of how a technical modification of a percutaneous device already being used with good clinical outcomes can have a significant impact not only from the standpoint of the parameters of technical results but also from the clinical viewpoint. Over the past 20 years of development of valves for transcatheter aortic valve implantation (TAVI) procedures we have witnessed a gradual technological progression where 2 different concepts—self-expanding valves and balloon-expandable valves—have initially achieved encouraging clinical outcomes in high-risk or inoperable patients,1,2 and gradually until achieving better short-term results compared to surgical aortic valve replacement in low-risk patients.3,4 This successful trajectory is partly due to the interest for developing and improving early and successive TAVI devices. The trials conducted among high-risk patients already found a higher rate of paravalvular leak after TAVI compared to surgical repair. As a matter of fact, it was a common event very much associated with a greater need for pacemaker implantation after TAVI2 in the early self-expandable valves. Conceptually this is something that could have been expected since there is no native valve resection or washout of the calcium remaining in the...